ANTARMUKA AKUISISI DATA TERISOLASI - , CINDERA PERMATANINGSIH; , Muhammad Arrofiq, S.T.,M.T.,Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The idea to create Isolated Data Acquisition Interface, a tool that has the advantage of being able to read a variety of voltage and current information on PLN distributed to households and industry and also in complete isolating signals, so if there is a problem on the input source electronic equipment and tools that will connect that in this case the load is not damaged or disturbed system works. Methods in isolating signals using ISO124P, The set of current and voltage sensors, inverting amplifier using Op-Amp IC LM741 so that the voltage in accordance with the ability of reinforced reader. In this case the oscilloscope has a voltage range that can be read is 40 VPP, then made the strengthening of a hundred times. From PLN 220 volt voltage scaled voltage of 11:511 times for sensors for voltage and current sensors use 15 watt resistor of 0.47 ohm so that the voltage at the load is not too reduced consumption. entry directly to the voltage sensor and to ISO124P ic current sensor after entering ISO124P enter it using LM741 operational amplifier with gain a hundred times so easy to read measuring instruments. This tool has a limit to the load current is 2 A and the frequency that can be read 25 kHz maximum.